2011
DOI: 10.1001/archpediatrics.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of Allergenic Foods and the Development of Reported Wheezing and Eczema in Childhood

Abstract: To examine whether the timing of introduction of the allergenic foods cow's milk, hen's egg, peanuts, tree nuts, soy, and gluten is associated with eczema and wheezing in children 4 years of age or younger. Design: Population-based prospective cohort study from fetal life until young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…Of the 17 papers included in the review, 11 were birth cohort studies . As the LISA birth cohort study generated 2 publications, the number of papers exceeds the number of study populations.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 papers included in the review, 11 were birth cohort studies . As the LISA birth cohort study generated 2 publications, the number of papers exceeds the number of study populations.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we have previously demonstrated that timing of introduction of food allergens and a dietary pattern including fish, vegetables, and fruit at age 14 months were not significantly associated with asthmalike symptoms in our cohort. 3,41 Also, the timing of introduction of fish showed no similarities with timing of introduction of other foods (Supplemental Table 9). This raises questions as to whether confounding by other diet factors plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…9 conducted a populationbased prospective cohort study(n=6905 children) in Netherlands and documented wheezing in 31% at age 2 years and in 14% at ages three and four years,while eczema was reported in 38%, 20%, and 18% of children at the ages of 2, 3, and 4 years, respectively. He found that the introduction of peanuts, tree nuts, hen's egg, cow's milk, gluten and soy before the age of 6 months was not signifi cantly associated with eczema or wheezing 9 . Early weaning had occurred in nearly one fourth(24.2%) of our children, and had no association with asthma occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,4,5 Asthma exacerbations by specifi c trigger factors are a well-known fact and how it affects their quality of life have been studied by Luskin AT et al 6 . Asthma exacerbations by asthma trigger factors have been documented by few studies 7,8,9,10,11 . This study was undertaken to identify the risk and trigger factors of asthma among school children of urban Mangalore.…”
mentioning
confidence: 99%